2019
DOI: 10.1002/mgg3.926
|View full text |Cite
|
Sign up to set email alerts
|

Novel SZT2 mutations in three patients with developmental and epileptic encephalopathies

Abstract: Background The seizure threshold 2 (SZT2) gene encodes a large, highly conserved protein that lowers seizure threshold and may also enhance epileptogenesis. In this study, three patients diagnosed with SZT2‐related developmental and epileptic encephalopathies (DEEs) were reviewed aiming to expand knowledge of the genotype and phenotype of SZT2 mutations. Methods Targeted next‐generation sequencing was performed to identify pathogenic mutations in 205 cases with DEEs of unknown etiology. Detailed clinical and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…It was initially suggested that SZT2 variants are associated with two distinctive MRI findings consisting of a thick and shortened corpus callosum (CC) along with a persistent cavum septum pellucidum (CSP) 2 . Subsequent accounts however failed to consistently describe those findings and reported normal imaging studies or different types of abnormalities including delayed myelination, dilated ventricles, atrophy, heterotopia, or subependymal nodules 6,12,13 . Both our patients had evidence of a persistent CSP on brain MRI with an abnormally short but not thickened CC in one of them.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…It was initially suggested that SZT2 variants are associated with two distinctive MRI findings consisting of a thick and shortened corpus callosum (CC) along with a persistent cavum septum pellucidum (CSP) 2 . Subsequent accounts however failed to consistently describe those findings and reported normal imaging studies or different types of abnormalities including delayed myelination, dilated ventricles, atrophy, heterotopia, or subependymal nodules 6,12,13 . Both our patients had evidence of a persistent CSP on brain MRI with an abnormally short but not thickened CC in one of them.…”
Section: Discussionmentioning
confidence: 73%
“…2 Subsequent accounts however failed to consistently describe those findings and reported normal imaging studies or different types of abnormalities including delayed myelination, dilated ventricles, atrophy, heterotopia, or subependymal nodules. 6,12,13 Both our patients had evidence of a persistent CSP on brain MRI with an abnormally short but not thickened CC in one of them. Interestingly, the detected CSP might not represent an incidental finding since it was reported to be a developmental anomaly that may contribute to epileptogenesis.…”
mentioning
confidence: 68%
See 3 more Smart Citations